THE PRINCIPLE OF NON-DISCRIMINATION IN HEALTH SERVICES IN THE PERSPECTIVE OF GOVERNMENT RESPONSIBILITY - Endang Wahyati Yustina; Anggraeni Endah Kusumaningrum (UNTAG Law Review, 2019)
Everyone has the right to receive health services. This is guaranteed in the 1945 Constitution. The government is responsible for making this happen through various health service efforts which include individual health service efforts and public health service efforts. The principle of non-discrimination in health services is a principle that originates from Human Rights. This principle must become the foundation in the implementation of health services, so that everyone must be treated equally and humanely and not discriminatory. Health services that are based on the principle of non-discrimination are the responsibility of the government through the implementation of government functions, in the form of regulation, implementation and supervision of the administration of health services. public services and general principles of good governance, one of which is the principle of non-discrimination. Therefore everyone has the right to get the same treatment to get the right to health services.